Subjective and objective evaluation of voice quality in patients with asthma - ÇELİKEL, TURGAY HÜSEYİN (MOSBY-ELSEVIER, 2007)
Objectives: To evaluate the voice quality in patients with mild-to-moderate asthma by subjective and objective methods. Study design: Comparative, controlled, cross-sectional study. Methods: Patients with mild-to-moderate asthma (n = 40) and age- and sex-matched healthy controls (n = 40) were included. Acoustic analyses were performed by the Multi-Dimensional Voice Program (MDVP; Kay Elemetrics Corporation, Lincoln Park, NJ) and the movements of the vocal cords were examined by videolaryngostroboscopy (VLS). In addition, the duration of illness, maximum phonation time, s/z values, and vital capacity were evaluated. Voice Handicap Index (VHI) and GRB scales were used for subjective evaluations. Results: Maximum phonation time values were significantly shorter both in male and female asthma patients compared with controls (P < 0.0001). Also, average shimmer values in MDVP were higher for both sexes in the patient group compared with controls (P = 0.002 and P = 0.04, respectively). There was a significant difference between female patients and sex-matched controls with regard to mean noise-to-harmonic ratio values (P = 0.006). Female patients with asthma had higher average jitter values compared with sex-matched controls (P < 0.0001). A significant difference was noted between asthma and control groups with regard to GRB scale (P < 0.0001, P < 0.001, and P < 0.0001, respectively). The VHI score was above the normal limit in 16 (40%), and VLS findings were abnormal in 39 (97.5%) asthmatics. Conclusion: In asthmatic patients, maximum phonation time, frequency, and amplitude perturbation parameters were impaired, but the vital capacity and the duration of illness did not correlate with these findings.
Keywords: asthma; dysphonia; acoustic analysis; GASTROESOPHAGEAL-REFLUX; TRIAMCINOLONE ACETONIDE; CHILDREN; AEROSOL